Whey Protein Isolate Supplementation While Endurance Training Does Not Alter Cycling Performance or Immune Responses at Rest or After Exercise - Forbes, Scott C.; Bell, Gordon J. (Frontiers in Nutrition, 2019)
This study examined whey protein isolate supplementation combined with endurance training on cycling performance, aerobic fitness and immune cell responses. Eighteen male cyclists were randomly assigned to either placebo or whey protein supplementation (WS). Both groups completed the identical endurance training program, 4 days per week for 6 weeks. Blood samples were obtained at rest and after 5 and 60 minutes of recovery from a simulated 40 km cycling time trial (TT) and were repeated after training. There were similar improvements in TT performance, peak oxygen uptake and ventilatory thresholds 1 and 2 after training in both groups. White blood cells (WBC) and neutrophils were elevated 5 minutes after the TT and continued to rise after 60 minutes (P<0.05). Training lowered WBC and neutrophils, 5 and 60 minutes after exercise (P<0.05). Lymphocytes increased 5 minutes after the TT and decreased below rest after 60 minutes of recovery (P<0.05). Training also lowered lymphocytes after 60 minutes of recovery. There was no change in natural killer cell activity with exercise, training or between groups. It was concluded that whey protein isolate supplementation while endurance training did not deferentially change cycling performance or the immune response at rest or after exercise. However, endurance training did alter performance, aerobic fitness and some post exercise immune cell response counts.